Importance interdisciplinary management of Diamond-Blackfan anemia and Cleft lip and palate sequel: Accompaniment of two years - Cristhian Ariel Cisneros Hidalgo; Gabriela Sotomayor Guaman; María del Pilar Bernal Pardo (Asociación Latinoamericana de Odontopediatría, 2019)
Cleft lip and palate (CLP) are the most common congenital craniofacial malformations. The Diamond-Blackfan anemia or congenital erythroblastic anemia is a selective red cell hypoplasia associated with heart, kidney, malformed hands, hypertelorism and stunted alterations. The presentation of Cleft lip and palate in patients with Diamond-Blackfan anemia is 10.3% of cases. Aim: To present a case report of a patient of 12 years with Diamond-Blackfan anemia and Cleft lip and palate sequel from the Interdisciplinary Clinic LPH of the Pontificia Universidad Javeriana (Bogota Colombia) where the interdisciplinary approach, behavior management and psychological support provided to the family were instrumental in achieving the expected therapeutic results. Results: Adherence to treatment and its success in supporting other health specialties during two years is slown. Conclusions: The multidisciplinary and interdisciplinary management with dental specialties, medical, and health in general for the management of patients with FLP and associated syndromes, it is important for successful treatment.